Geraniol suppresses proinflammatory mediators in phorbol 12-myristate 13-acetate with A23187-induced HMC-1 cells - Huang Y; Yang XL; Ni YH; Xu ZM (Dove Medical Press, 2018)
Yue Huang, Xiao-Lin Yang, Yi-Hua Ni, Zheng-Min Xu Department of Otolaryngology-Head and Neck Surgery, Children’s Hospital of Fudan University, Shanghai, China Background: Geraniol is a monoterpene alcohol that has anti-fungal, anti-cancer and anti-nociceptive properties, but its anti-allergic rhinitis (AR) property is unclear.Methods: In this study, the anti-inflammatory role and its possible mechanisms of geraniol in human mast cell line (HMC-1) cells stimulated by inflammatory trigger phorbol 12-myristate 13-acetate plus A23187 (PMACI), as well as in ovalbumin (OVA)-induced AR mice models were investigated.Results: PMACI results in a significant increase in the production of proinflammatory cytokines, such as TNF-α, IL-1β, MCP-1, IL-6 and as well as histamine. Geraniol was found to inhibit both TNF-α, IL-1β and IL-6 protein and mRNA expressions at concentrations of 40, 80, 160 μM. In OVA-induced AR models, geraniol treatment was able to suppress AR biomarkers (OVA-specific IgE and IL-1β as well as histamine) and nasal rub scores. Interestingly, p38, a member of the mitogen-activated protein kinase (MAPK) signaling family, was found to be increasingly hypophosphorylated as geraniol dose was increased. Similar decreases in the nuclear level of p65, a member of the nuclear factor kappa B (NF-κB) signaling pathway, were also observed.Conclusion: Our data highlights that the anti-inflammatory properties of geraniol on AR-related markers in activated HCM-1 cells and OVA-induced AR models may be mediated through the regulation of the MAPK/NF-κB signaling pathway. Keywords: geraniol, HMC-1, allergic rhinitis, PMACI